EVALUATION OF EXISTING TEACHING METHODS USED FOR LECTURE CLASSES IN PHARMACOLOGY - DR. HANMANT S. AMANE; DR. SHILPA N. KAORE; DR. SURESH V. VASVANI (International Journal of Pharma and Bio Sciences, 2013)
To evaluate the existing teaching methods in pharmacology viz. classes using overhead projector and transparencies, classes using chalkboard, and classes utilizing PowerPoint presentations. A questionnaire was designed and provided to second year medical students at a medical college. They were asked to fill the questionnaire and to evaluate different teaching methods used in pharmacology and also they were free to make suggestions and write their own opinion. The results were compared to find out the best method for understanding the subject according to students’ opinion As per the subjective assessment of the teaching methods, students preferred computer and PowerPoint presentations the most. Many students also suggested use of chalkboard for explaining the topic & use of PowerPoint presentations for explaining diagrams & flowcharts. According to students’ opinion, the best method for understanding and retaining the subject is PowerPoint presentations.